2010
DOI: 10.1097/won.0b013e3181c68c89
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Costs and Effects of a Nutrient-Based Skin Care Program As a Component of Prevention of Skin Tears in an Extended Convalescent Center

Abstract: The NBSC had a lower projected cost for prevention of skin tears and more skin-tear-free days when compared with non-NBSC products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Caring for people with fragile skin is a challenge when a minor trauma can result in Skin Tear (ST) (1)(2)(3) . Although some researchers suggest that Skin Tear is more prevalent than pressure ulcers and burns (4)(5) , ST go unnoticed as they are shallow traumatic wounds, occurring mainly in elderly ends resulting from friction or a combination of friction and shear, leading to separation of the epidermis from the dermis (partial thickness wound) or completely separating the epidermis and the dermis from the underlying structures (total thickness wound) (6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caring for people with fragile skin is a challenge when a minor trauma can result in Skin Tear (ST) (1)(2)(3) . Although some researchers suggest that Skin Tear is more prevalent than pressure ulcers and burns (4)(5) , ST go unnoticed as they are shallow traumatic wounds, occurring mainly in elderly ends resulting from friction or a combination of friction and shear, leading to separation of the epidermis from the dermis (partial thickness wound) or completely separating the epidermis and the dermis from the underlying structures (total thickness wound) (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Simple measures such as the identification of patients at risk and the implementation of prevention protocols are proving to be effective to prevent ST or minimize its severity (12) . Researches (1,13) show that the occurrence of ST decreases as soon as an individual is identified at risk and preventive measures are implemented.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve this uncomfortable situation, an effective strategy should be established for the prevention of skin tears. One prospective pre‐post intervention study investigated the cost effectiveness of a nutrient‐based skin care regimen for skin tear prevention among institutionalized elderly residents in an extended care facility . Another pre‐post intervention study showed a possible prevention strategy for skin tears, including staff education, skin sleeves, padded side rails, gentle skin cleansers and lotion use among elderly patients .…”
Section: Introductionmentioning
confidence: 99%
“…However, the tape should be gentle enough that removal should not cause skin trauma to the face and eyelids. Medical adhesive related skin injuries are estimated to impact at least 1.5 million patients annually in the US with significant costs per incident [5]. …”
Section: Introductionmentioning
confidence: 99%